2010
DOI: 10.1359/jbmr.090805
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow changes in adolescent girls with anorexia nervosa

Abstract: Early osteoporosis is common among adolescent girls with anorexia nervosa (AN) and may result from premature conversion of red (RM) to yellow bone marrow. We performed right knee magnetic resonance imaging (MRI) on a 1.0 T extremity scanner in 20 patients and 20 healthy controls, aged 16.2 ± 1.6 years (mean ± SD). Coronal T1-weighted (T1W) images and T1 maps were generated from T1 relaxometry images. Blinded radiologists visually assessed RM in the distal femoral and proximal tibial metaphyses in T1W images us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
85
0
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 136 publications
(98 citation statements)
references
References 38 publications
9
85
0
4
Order By: Relevance
“…However, no relationship between serum parameters and changes in marrow adiposity is expected. This is due to the current understanding that, in contrast with other types of fat, the role and function of marrow fat are independent of general body mass or changes in levels of serum lipids [33,34]. In fact, in their study, Syed et al [9] found that changes in serum leptin in either group did not correlate with changes in bone or adipocyte parameters.…”
Section: Discussionmentioning
confidence: 93%
“…However, no relationship between serum parameters and changes in marrow adiposity is expected. This is due to the current understanding that, in contrast with other types of fat, the role and function of marrow fat are independent of general body mass or changes in levels of serum lipids [33,34]. In fact, in their study, Syed et al [9] found that changes in serum leptin in either group did not correlate with changes in bone or adipocyte parameters.…”
Section: Discussionmentioning
confidence: 93%
“…It has been suggested that the role of BMF is distinct from that of visceral and subcutaneous adiposity. This hypothesis is supported by studies in anorexia nervosa (AN) patients, in which extreme low body fat mass (including VAT and SAT) is present [50]. Not only do AN patients have a high prevalence of osteoporosis, but there is also a high vertebral BMF content.…”
Section: Bmf and Other Fat Tissuementioning
confidence: 87%
“…Eckuland et al described unequivocal augmenttation of marrow fat in a group of adolescents with anorexia nervosa in comparison to a control group (99). In another study, the investigation of the hormonal/ metabolic profile of patients with anorexia nervosa showed normal insulin sensitivity and increased levels of serum adiponectin in relation to normal weight control women (100).…”
Section: Bone and Energy Metabolismmentioning
confidence: 99%